1980
DOI: 10.1097/00006842-198003000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Menstruation

Abstract: An attempt was made to relate personality to premenstrual tension (PMT), using two groups of 40 parous and 40 mulliparous women, respectively composed of 20 single and 20 married subjects with an age range of 21 to 30 years. The menstrual instruction group had identical age range and means with the nonmenstrual group. Control for pregnancy, use of contraceptives, and irregularity of periods was by exclusion. The influence of civil status and parity was also examined. Standard measures of personality and anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Another psychological factor correlating to premenstrual mood changes is that women who complained of premenstrual negative mood changes had a stronger level of anxiety than controls (Awaritefe, Awaritefe, Lib, Diejomach, & Ebie, 1980). The results of our study were consistent with this; premenstrual mood changers felt greater anxiety about pregnancy or childbearing.…”
Section: Discussionsupporting
confidence: 86%
“…Another psychological factor correlating to premenstrual mood changes is that women who complained of premenstrual negative mood changes had a stronger level of anxiety than controls (Awaritefe, Awaritefe, Lib, Diejomach, & Ebie, 1980). The results of our study were consistent with this; premenstrual mood changers felt greater anxiety about pregnancy or childbearing.…”
Section: Discussionsupporting
confidence: 86%
“…However, this study reports no measure of ovulation and obtained only two measures of psychological "state" for each menstrual cycle. Awaritefe et al (30), using a design similar to Golub's but including parous and nulliparous women, found that state and trait anxiety were significantly related and that parity accounted for as much variance as cycle phase. Golub had included only parous women, which suggests that this subgroup may be physiologically different enough that trait anxiety loses influence.…”
Section: Discussionmentioning
confidence: 99%